Disclosure of Conflict of Interest Regarding the paper “Per- and Poly-fluoroalkyl Substances (PFAS) Exposure and Risk of Kidney, Liver, and Testicular Cancers - Marcolungo, Claudia; Boffetta, Paolo (La Medicina del Lavoro, 2024)
-